Home range and movement of juvenile black-faced spoonbill Platalea minor in South Korea. Issue 1 (December 2017) - Kang, Jung-Hoon; Kim, In; Lee, Ki-Sup; Kwon, In-Ki; Lee, Hansoo; Rhim, Shin-Jae
Abstract This study was conducted to clarify the size of the home range and movement distance of juvenile black-faced spoonbills from post-fledging until fall migration using a Global Positioning System (GPS)-wideband code division multiple access (WCDMA)-based telemetry system along the west coast of South Korea. The home range of juvenile black-faced spoonbills (n  = 3) was 45.2 km2 in size and the core area consisted of 8.4 km2 within the Baeksu mudflat, Yeonggwang, South Jeolla Province, South Korea. Mean weekly movement distances were not significantly different (Kruskal–Wallis test, Z  = 3.47, P  = 0.18) among individuals, ranging from 0.1 to 23.9 km during the study period. The home range and movement of juvenile black-faced spoonbills were related to intertidal areas, especially to their use as feeding areas.